ST2 regulates allergic airway inflammation and T-cell polarization in epicutaneously sensitized mice. - Savinko, T; Karisola, P; Lehtimäki, S; Lappeteläinen, A; Haapakoski, R; Wolff, H; Lauerma, A; Alenius, H (2013)
IL-33 is an inducer of proinflammatory and T-helper type 2 (Th2) cytokines, which have an important role in atopic dermatitis (AD) and allergic asthma. ST2 is a specific receptor for IL-33 and is expressed on Th2 cells, eosinophils and mast cells. A murine model of AD was used to characterize the role of ST2 in allergen-induced skin inflammation and allergic asthma. ST2-/- and wild-type (WT) mice were epicutaneously sensitized with ovalbumin (OVA) and staphylococcal enterotoxin B, and intranasally challenged with OVA. ST2-/- mice exhibited increased production of IFNγ and increased number of CD8(+) T cells in the sensitized skin and in the airways compared with WT mice. The number of eosinophils was decreased, and Th2 cytokines were downregulated in the airways of epicutaneously sensitized ST2-/- mice compared with WT controls. However, dermal eosinophil numbers were as in WT, and the levels of Th2 cytokines were even elevated in the sensitized skin of ST2-/- mice. ST2-/- mice had elevated numbers of neutrophils and macrophages and increased levels of proinflammatory cytokines in the sensitized skin. The role of ST2 differs between different target tissues: ST2 is dispensable for the development of Th2 response in the sensitized skin, whereas it is a main inducer of Th2 cytokines in asthmatic airways.